Birds of Peru : Revised and Updated Edition - Schulenberg, Thomas S. (Book collections on Project MUSE., 2007)
Nearly eighteen hundred different bird species--one fifth of the world's birds--have been recorded in Peru. Birds of Peru is the most complete and well-researched field guide to this rich and fascinating diversity. It illustrates every one of the 1,792 species and shows the distinct plumages of each. It includes 304 superb, high-quality color plates directly opposite concise descriptions and color distribution maps, making it much easier to use in the field than standard neotropical field guides. The detailed text discusses key identification features, status, distribution, and vocalizations for all species, and many subspecies.